(untitled) (Scientific journal of the Fergana State University, 2024)
The article presents information about the study of the problem of the educational environment and the influence of environmental safety on the student, the methodological and theoretical foundations of the psychological safety of the educational environment. The empirical results of E. N. Gilemkhanova “Index of sociocultural safety of schoolchildren” were obtained through the scales of socio-psychological vulnerability, socio-psychological disintegration, virtual autism and are presented on the basis of the data. An analysis of differences in the index of social and cultural security among high school students is also given.